2017
DOI: 10.17113/ftb.55.02.17.4722
|View full text |Cite
|
Sign up to set email alerts
|

Relationships among Bioactive Compounds Content and the Antiplatelet and Antioxidant Activities of Six Allium Vegetable Species

Abstract: SummaryAllium sp. vegetables are widely consumed for their characteristic flavour. Additionally, their consumption may provide protection against cardiovascular disease due to their antiplatelet and antioxidant activities. Although antiplatelet and antioxidant activities in Allium sp. are generally recognised, comparative studies of antiplatelet and antioxidant potency among the main Allium vegetable species are lacking. Also, the relationship between organosulfur and phenolic compounds and these biological ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 29 publications
3
35
0
2
Order By: Relevance
“…Despite the differences in the volatile sulfur composition, many components are highly similar for both species, as expected, since they are genetically closely related [38]. The volatile sulfur compounds identified in current study are known to be responsible for typical flavor and odor of onions [27,39], as well as for their strong biological activity [17,[40][41][42][43][44]. Some of the relevant Allium species with their volatile sulfur compounds are described in the following section (Data S2).…”
Section: Nosupporting
confidence: 61%
“…Despite the differences in the volatile sulfur composition, many components are highly similar for both species, as expected, since they are genetically closely related [38]. The volatile sulfur compounds identified in current study are known to be responsible for typical flavor and odor of onions [27,39], as well as for their strong biological activity [17,[40][41][42][43][44]. Some of the relevant Allium species with their volatile sulfur compounds are described in the following section (Data S2).…”
Section: Nosupporting
confidence: 61%
“…Beretta et al. (2017) performed a comparative analysis of antioxidant activity among Allium vegetable species and determined 2.47 and 13.43 ”M TE/g for leek and garlic aqueous extracts, respectively. Morales‐Soto et al.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the well antioxidant activity showed by Allium depends on the chemical structure, the mass fraction of each single phenolic compound and the combinations and interactions among phenolic (Beretta et al, 2017). It was indicated that rosmarinic acid, p-hydroxybenzoic acid, and protocatechuic acid all were identified as major phenolic compounds of Allium extract, and these compounds were contributors to the antioxidant activities (Mollica, Zengin, Locatelli, Picot-Allain, & Mahomoodally, 2018).…”
Section: Total Phenolic Content and Total Flavonoid Contentmentioning
confidence: 99%
“…Phenolic and flavonoid, the most important plant secondary metabolites, have the potential health benefits to human body and display high correlations in the inhibition or management of many chronic diseases(Rahman, Costa de Camargo, & Shahidi, 2018). Previous studies indicated that the antioxidant action of Allium plants was strongly and positively correlated with the existence of polyphenols.Additionally, the well antioxidant activity showed by Allium depends on the chemical structure, the mass fraction of each single phenolic compound and the combinations and interactions among phenolic(Beretta et al, 2017). It was indicated that rosmarinic acid, p-hydroxybenzoic acid, and protocatechuic acid all were identified as major phenolic compounds of Allium extract, and these compounds were contributors to the antioxidant activities(Mollica, Zengin, Locatelli, Picot-Allain, & Mahomoodally, 2018).…”
mentioning
confidence: 99%